Saving the moral self: Unethical leadership and employee behaviors – a moral cleansing perspective - Shakil Adnan Malik; Samina Nawab; Khurram Shafi (European Journal of Management and Business Economics (EJM&BE), 2023)
Purpose - The purpose of this study is to investigate the concept of vicarious moral cleansing and scrutinize whether unethical behavior of leaders initiate moral cleansing in subordinates or not. This study also highlights a boundary condition under which employees are motivated to cleanse their moral self-image through increased organizational citizenship behaviors and decreased counterproductive work behaviors. Design/methodology/approach The study is quantitative based on hypothesis testing. By adopting convenience sampling technique, employees working at all managerial levels of service sector organizations were asked to fill out the questionnaires. Being a time-lagged study, data for independent variable (unethical leadership) and moderator (relational self-construal) were collected at T1, data for mediator (moral self-image) were collected at T2 and data for outcomes (OCBs, CWBs) were collected at T3 from same respondents. To rule out the possibility of common method bias and social desirability bias, a multi-wave design was adopted and respondents were asked to provide unique keys/IDs instead of their names. Findings This study investigated the impact that unethical leaders impose on employee self-concept. Moreover, this study also explored the motivational tendencies of moral self-image. Findings suggest that employees' desirable or undesirable behaviors against leader are dependent upon the perceptions related with their own role, self-image and perception of leader's integrity and intentions. Leader's unethicality is perceived threatening for their own moral self-image and they deal with it constructively. This study has laid the foundation for presence of vicarious moral cleansing in organizational setup, and it is advised that researchers must investigate this phenomenon in different settings to provide useful insights. Research limitations/implications Due to lack of resources, employing a pure longitudinal research design was not feasible, and therefore a time-lagged research design was used to gather data from only two cities of Pakistan. However, authors believe that a longitudinal research design, with data collection from a larger sample, will provide more fine-grained results. Secondly, use of perceived leader's integrity scale to measure unethical leadership is another limitation. Although the authors tried to address this issue by conducting an EFA and adopting only suitable items, yet a new scale which is able to measure the true essence of unethical leadership ought to be developed. Originality/value Use of moral self-image as an indicator of moral cleansing is an additional contribution of this study, as previous studies used levels of guilt as driving force behind moral cleansing and compensatory cleansing. Most of the studies on unethical leadership as well as moral cleansing took place in the Western context and scholars' stress that culture can substantially influence outcomes of these constructs. Thus, this study extends the literature on moral cleansing and moral self-regulation by developing and testing a model in cultural settings of Pakistan.
Keywords: 650; Moral cleansing; Moral self-image; Self-construal; Unethical leadership